Knockout of the c-Jun N-terminal Kinase 2 aggravates the development of mild chronic dextran sulfate sodium colitis independently of expression of intestinal cytokines TNFα, TGFB1, and IL-6 - Kersting S; Reinecke K; Hilgert C; Janot MS; Haarmann E; Albrecht M; Müller AM; Herdegen T; Mittelkötter U; Uhl W; Chromik AM (Dove Medical Press, 2013)
Sabine Kersting,1 Kirstin Reinecke,2 Christoph Hilgert,1 Monika S Janot,1 Elisabeth Haarmann,1 Martin Albrecht,1 Annette M Müller,3 Thomas Herdegen,2 Ulrich Mittelkötter,1 Waldemar Uhl,1 Ansgar M Chromik11Department of General and Visceral Surgery, St Josef Hospital, Ruhr-University of Bochum, Bochum, Germany; 2Institute of Experimental and Clinical Pharmacology, University Hospital of Schleswig-Holstein, Campus Kiel, Germany; 3Department of Pediatric Pathology, Rheinische Friedrich-Wilhems-University of Bonn, Bonn, GermanyIntroduction: The c-Jun N-terminal kinases (JNKs) are involved in signal transduction of inflammatory bowel diseases. The aim of this study was to examine the function of JNKs by using a low-dose dextran sulfate sodium (DSS) model in JNK1 knockout mice (Mapk8–/–), JNK2 knockout mice (Mapk9–/–), and wild-type controls (WT1, WT2).Methods: The animals were evaluated daily using a disease activity index. After 30 days, the intestine was evaluated histologically with a crypt damage score. CD4+ and CD8+ cells were quantified using immunofluorescence. Analysis of tumor necrosis factor-a (TNFα), interleukin-6 (IL-6), and transforming growth factor ß1 (TGFB1) expression was carried out using LightCycler® real-time polymerase chain reaction.Results: Cyclic administration of low-dose DSS (1%) was not able to induce features of chronic colitis in Mapk8–/– WT2 mice. By contrast, DSS administration significantly increased the disease activity index in WT1 and Mapk9–/– mice. In Mapk9–/– mice, the crypt damage score and the number of CD4+ and CD8+ cells as features of chronic colitis/inflammation were also significantly elevated. Expression of TNFα, IL-6, and TGFB1 was not altered by the JNK knockout.Conclusion: Administering DSS at a defined low concentration that is unable to induce colitis in WT animals leads to clinically and histologically detectable chronic colitis in Mapk9–/– mice. The reason for this disease-inducing effect resulting from the loss of JNK2 remains to be elucidated. Expression of TNFα, IL-6, and TGFB1 does not appear to be involved; proapoptotic JNK2 may prolong the activity of proinflammatory immune cells, leading to perpetuation of the inflammation.Keywords: inflammatory bowel diseases, proinflammatory cytokines, JNK knockout mice, T-cell immune response